Class size in high school English, methods and results - Smith, Dora V. (Dora Valentine), 1893-1985 (University of Minnesota Press, 1931)
Class Size in High School English, Methods and Results was first published in 1931. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. More than half this book consists of concrete description of methods found useful in teaching classes of fifty or more pupils in ninth grade English. Subjects dealt with include the care of individual differences, assignment and motivation of work, stimulating pupil participation, insuring activity and variety in class work, and arranging for individual and group competition. Dr. Smith shows how different methods may be adapted to classes of different sizes, and also presents new data on relative opportunity and relative achievement of pupils in large and small classes, relative attitudes and character traits revealed by pupils, and comparative strain on the teacher in the different types of classes. The volume includes a complete account of all class size studies that appeared up to the middle of 1930, also analysis of trends in class size in high schools as revealed through published reports and through the hitherto unpublished study made by Dr. Earl Hudelson in 1929. Dr. Smith is specialist in secondary school English under the National Survey of Secondary Education."It is rich in suggestion of methods of teaching to be used with large and small classes in English, and, by inference, in other fields of instruction," Leonard V. Koos, University of Chicago."Very useful and carefully work out techniques for handling large classes," Allan Abbott, Teachers College, Columbia University